Orientalisme Dalam Hadis - Fikri, Shofil; P.J, Aulia Rosferyn Mufidah; Rahmaputri, Nanda Aulia; H, M Wildan Qolbi; Nugroho, M. Seto; Akbar, M. (CV. ITTC INDONESIA, 2024)
Orientalism is research carried out by non-Muslims on aqidah, Shari'a, language and the development of Islam which is based on several motives, namely religion, science, economics and politics which aims to distance people from the true religion by fostering doubts about religion. Islam. Orientalism emerged around the 7th century H in Andalusia (Spain) when Christians put pressure on Muslims which resulted in Muslims doubting that the crusades were not finished. Through orientalism, the figures destroy the faith that already exists in the hearts of Muslims and instill the feeling that Islam is dangerous for them.